Pandangan Ulama Nagari Lasi terhadap (Surat Edaran Dirjen Bimas Islam Kemenag No: P-005/DJ.III/HK.00.7/10/2021) Prosedur Pernikahan Suami dalam Masa Iddah Istri Ditinjau dari Fikih Munakahat - Amiratun Nabilah; Fauzan (AHKAM, 2026)
Although Circular of the Director General of Islamic Community Guidance of the Ministry of Religious Affairs Number P-005/DJ.III/HK.00.7/10/2021 concerning the procedure for a husband’s marriage during his wife’s ‘iddah period has received attention in Islamic family law scholarship, research on local Islamic scholars’ views of this provision from the perspective of Islamic marital jurisprudence remains limited. This study aimed to analyze the views of Islamic scholars in Nagari Lasi regarding the provisions of the circular and to examine them from the perspective of Islamic marital jurisprudence. This study employed a descriptive qualitative approach using field research. The informants comprised nine Islamic scholars and religious leaders in Nagari Lasi who were selected purposively. Data were collected through interviews, observation, and documentation and were subsequently analyzed through data reduction, data presentation, and conclusion drawing. The findings showed that two informants supported the provisions of the circular, whereas seven informants did not support them. The supporting group emphasized the protection of women’s rights, the fulfillment of post-divorce obligations, and the prevention of concealed polygamy. Conversely, most informants maintained that men are generally not subject to an ‘iddah period as women are, except under certain circumstances involving a māni‘ syar‘i. These findings reveal differing views regarding the positioning of Islamic jurisprudential provisions and considerations of women’s rights protection as the basis for assessing this administrative policy. This study broadens the scholarship on Islamic marital jurisprudence by clarifying the relationship among Islamic jurisprudential provisions, administrative policy, and the protection of post-divorce rights, while providing opportunities for further research encompassing broader geographical areas, informant groups, and institutional perspectives.